A critical assessment of the potential vertical transmission hypotheses: Implications for research on the early-life infection with COVID-19. (November 2021) - Yang, Mengqin; Wang, Qiuqin; Song, Yulei; Zou, Minyan; Li, Yan; Xu, Guihua; Yan, Ting; Bai, Yamei
Abstract: The risk of potential vertical transmission in SARS-CoV-2 infected pregnant women is currently a topic of debate. To explore the correlation between the two, we searched PubMed, Embase®, and Web of Science for studies on vertical transmission of COVID-19. The quality of the studies was evaluated by the Cochrane risk of bias tool. Detailed information of each included case including methods of delivery, protection measures for mothers and neonates at birth, types of specimens, inspection time, results of testing and feeding patterns was collected to assess the possibility of vertical transmission. The results showed that of the 390 neonates reported in 36 studies, 23 were infected with SARS-CoV-2 by potential vertical transmission. From the perspective of virology and pathology, vertical transmission of SARS-CoV-2 was possible via uterus or breastmilk. Some reported potential vertically transmitted neonates could be attributed to horizontal transmission. It is extremely vital to fully elucidate the potential routes of transmission of SARS-CoV-2, implicating clinical practice and nursing to reduce the risk of not only horizontal transmission but also vertical transmission, thus protecting neonates from COVID-19 infection. Highlights: 23 out of 390 neonates were suspected vertically transmitted. SARS-CoV-2 was possible via intrauterine infection or breastfeeding. A better understanding of vertical transmission for COVID-19. Promoting maternal and fetal health.